Convertible Bonds - Chang, Fook Chin, Glen (2010)
The financial meltdown due to credit crunch in 2008 was in which has shaken the entire global financial industry, sparing no one (from investors, to top executives, to junior bank staff, to all stakeholders). What is unbelievable to me is not the intensity of the impact of credit crunch on the entire global system. What appalls me is the shocking revelation that many investors of Lehman Brother mini-bonds do not really know what they have invested their money in. If Lehman Brothers had not failed and collapsed, many would still think they have bought a ‘guaranteed’ investment product. This led me to doing this thesis on a financial instrument (convertible bonds) that is not familiar among retail investors, particular among those that are not so invest-savvy. The thesis aims to give an average non invest-savvy retail investor a better idea of this financial instrument before making decision in investing in it. Convertible Bonds is one of the types of Convertible Securities, a category of new financial products that was birthed from the process of Financial Engineering. The name ‘Convertible Bonds’ has been a new name heard in the financial markets in recent years but little of it has been heard among the retail investors’ public. The objective of this dissertation paper is to explore the characteristics of this new instrument that a retail investor should now as well as advantages and disadvantages of investing in it. We will also look at the reasons why some companies choose to issue this instrument instead of a straight bond or equity (common stock). What we can see in this paper, therefore, will be the features of a convertible bond, its evolution and history, why issuers issue them, what an investor should know about investing in them as well as the recommended way to invest in such a complicated/ exotic financial product.